Production of biodiesel from chicken tallow - Kau Juelun (School of Environmental Engineering, University Malaysia Perlis, 2013)
In the research, waste chicken tallow is used as the low cost sustainable potential feedstock for biodiesel production. Alkali transesterification or methanolysis is the main process to produce the biodiesel in the research.